Perianaesthetic complications associated With adenotonsillectomy at the University College hospital, Ibadan, Nigeria. (2012)
Adenoidectomy and tonsillectomy are common ear, nose and throat operations in children and are often accompanied by complications. This study assessed the perianaesthetic complications encountered among patients who had adenotonsillectomy in a tertiary hospital through May 2009 to April 2010.The study comprised of 49 subjects made up of 26 (53%) males and 23 (47%) females with a median age 36 (range=8 – 64) months and a median weight of 14kg (range = 5 –76kg). All the patients had general anaesthesia with endotracheal intubation. The procedures included tonsillectomy in 8 (16%) subjects, adenoidectomy in 18 (37%) and adenotonsillectomy in 23 (47%). Of the 49 patients, 24 (49%) had associated OSA, 2 (4%) had sickle cell disease, 1 (2%) patient had Down’s syndrome and 1 (2%) had hypertension. The estimated median blood loss was 50ml with a range of 20-200ml. The incidence of critical events and complications was 53.1%. Vomiting was the most common complication, occurring in 16% of the patients, followed by accidental tube dislodgement 14% and tube compression 10%. The use of plastic endotracheal tube was significantly associated with the occurrence of tube compression compared to the reinforced (non-kinkable) tube (Fisher’s exact=0.034), in addition, the presence of OSA is significantly associated with delayed post-operative recovery (Fisher’s exact = 0.05).We conclude that there is a high incidence of tube compression and dislodgement complicating adenotonsillectomy suggesting the need to modify the method of anchoring the endotracheal tube during the procedure.